(untitled) (Journal of the College of Basic Education, 2024)
The Crusaders have erealized since the yset foot in the Levant in the late eleventh century AD Fifth Hijri , the need to preserve different water sources And the multiplicity in the region, especially in the parts they occupied, and is represented in Edessa and Antioch Beit Al-Maqdis , and Tripoli, and in order for their presence there to continue, it is necessary to strive towards subjugating the headwaters of the Rivers or their estuaries. And depriving Muslims - as much as possible - of enjoying the advantages of the vital strategic water site